2014
DOI: 10.1111/deci.12070
|View full text |Cite
|
Sign up to set email alerts
|

Failure Risk and Quality Cost Management in Single versus Multiple Sourcing Decision

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link: ABSTRACTThe advantage of multiple sourcing to protect against supplier failures arising from undependable products due to latent defects is examined using a model with non-linear external failure costs. Prior research has focused only on supplier failures arising from unreliable supply, such as late/insufficient/no delivery. I derive a closed-form characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…A latest example is Zhou, Tao, Zhang, and Cai (2016) who study a hybrid mechanism that combines a uniform-price reverse auction with flexible noncompetitive contracts; their mechanism awards multiple winners because each supplier only provides one unit, which is quite different from our dual-sourcing model where each supplier can provide multiple units and the buyer allocates quantities endogenously to mitigate supply risk. In fact, there are other operational reasons for splitting awards in reverse auctions, including suppliers' convex production costs (e.g., Tunca & Wu, 2009), capacity constraints (e.g., Chaturvedi, 2015), supplier retention (e.g., Chaturvedi, Beil, & Martínez-de-Albéniz, 2014), reducing external failure costs caused by defective products (e.g., Yim, 2014), or other given policies (e.g., Gupta, Chen, Dawande, & Janakiraman, 2015). Our study differs from the above papers in that the characteristic of dual-sourcing auction design is supply risk mitigation.…”
Section: Literaturementioning
confidence: 99%
“…A latest example is Zhou, Tao, Zhang, and Cai (2016) who study a hybrid mechanism that combines a uniform-price reverse auction with flexible noncompetitive contracts; their mechanism awards multiple winners because each supplier only provides one unit, which is quite different from our dual-sourcing model where each supplier can provide multiple units and the buyer allocates quantities endogenously to mitigate supply risk. In fact, there are other operational reasons for splitting awards in reverse auctions, including suppliers' convex production costs (e.g., Tunca & Wu, 2009), capacity constraints (e.g., Chaturvedi, 2015), supplier retention (e.g., Chaturvedi, Beil, & Martínez-de-Albéniz, 2014), reducing external failure costs caused by defective products (e.g., Yim, 2014), or other given policies (e.g., Gupta, Chen, Dawande, & Janakiraman, 2015). Our study differs from the above papers in that the characteristic of dual-sourcing auction design is supply risk mitigation.…”
Section: Literaturementioning
confidence: 99%
“…The specific supply-defect risk addressed in these pages is relatively new to the literature. Whereas several recent studies have investigated the causes and consequences of defects (e.g., [7,5,40]), the only study treating defect as a supply risk and proposing diversification as a mitigating strategy is that of Yim [51]. Yim [51] proposed a multiple-supplier procurementallocation model that minimizes a risk-averse cost function that quadratically increases with the number of defects.…”
Section: Diversification Of Supply Riskmentioning
confidence: 99%
“…Whereas several recent studies have investigated the causes and consequences of defects (e.g., [7,5,40]), the only study treating defect as a supply risk and proposing diversification as a mitigating strategy is that of Yim [51]. Yim [51] proposed a multiple-supplier procurementallocation model that minimizes a risk-averse cost function that quadratically increases with the number of defects. Where a design error is responsible for defects, Kang et al [23] showed that the defect risk is exponentially amplified where a common design is shared among different products.…”
Section: Diversification Of Supply Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers' interest has also been drawn to complaints related to latent defects with no discovered reason [14], false failure returns [15] and the impact of supplier production rate on defects and production costs [16]. When studying human factors, Mateo et al [17], using production data, found that there is no significant relation between complaints and absenteeism, and Gajdzik and Sitko [18] found a relation between complaints and human errors in steel sheets manufacturing.…”
Section: Introductionmentioning
confidence: 99%